PPARγ: a circadian transcription factor in adipogenesis and osteogenesis - Kawai, Masanobu (2010)
Peroxisome proliferator-activated receptor γ (PPARγ) is a critical factor for adipogenesis and glucose metabolism, but accumulating evidence demonstrates the involvement of PPARγ in skeletal metabolism as well. PPARγ agonists, the thiazolidinediones (TZDs), have been widely used for the treatment of type 2 diabetes mellitus owing to their effectiveness in lowering blood glucose. However, the use of TZDs has been associated with bone loss and fractures. TZD-induced alterations in the bone marrow milieu—that is, increased marrow adiposity with suppression of osteogenesis—could partially explain the pathogenesis of TZD-induced bone loss Furthermore, several lines of evidence place PPARγ at the center of a regulatory loop between circadian networks and metabolic output. PPARγ exhibits a circadian expression pattern that is magnified by consumption of a high-fat diet. One of the circadian-regulated genes expressed in peripheral tissues, nocturnin (Noc), has been shown to enhance PPARγ activity. Importantly Noc-deficient mice are protected from diet-induced obesity, exhibit impaired circadian expression of PPARγ and have increased bone mass. This Review focuses on new findings regarding the role of PPARγ in adipose tissue and skeletal metabolism and summarizes the emerging role of PPARγ as an integral part of a complex circadian regulatory system that modulates food storage, energy consumption and skeletal metabolism.